Nanocubos de óxido de cobre: influência do tamanho na atividade eletrocatalítica para a oxidação de metanol - COSTA, Isael Pereira (2022)
The surface area and shape of nanocrystals significantly impact fuel cell performance. However, other parameters can affect their activities and must be considered. Thus, it was demonstrated that the presence of crystalline defects (such as oxygen vacancies) and the relative concentration of Cu(I)/Cu(II) could also vary with decreasing size of CuxO nanocubes (NCs–CuxO). However, such differences did not follow the size as expected, showing that this parameter does not play a critical role in determining material properties. NCs–CuxO with controlled sizes (50, 65 and 85 nm) were synthesized by a simple and similar protocol, leading to nanocrystals with {100} surfaces to study such phenomena. When the catalytic activity of NCs–CuxO of different sizes was evaluated in the electrooxidation of methanol in an alkaline medium, there was a decrease in the performance observed for NCs–CuxO: 50 nm > 85 nm > 65 nm, in which NCs–CuxO of 50 nm led to the best electrocatalytic results. Interestingly, our results showed that the differences in the catalytic activities of NCs–CuxO with different sizes could not be attributed only to a gain in surface area with a decrease in particle size. More specifically, the XPS results indicated that particle size reduction led to an increase in surface oxygen/structural oxygen and Cu(I)/Cu(II) ratios, demonstrating the enrichment of oxygen vacancies on the surface of NCs– CuxO, which also contributed to the observed catalytic activities. The above findings provide a deeper understanding of particle size on the performance of nanomaterials and offer new ideas for designing efficient electrocatalysts for fuel cells.